The battle of the bookshops : a novel - Alexander, Poppy (Avon, an imprint of HarperCollinsPublishers, 2025)
"A charming literary-themed novel about a young woman determined to save her great-aunt's beloved bookshop from extinction by the shiny new competition-which also happens to be run by the handsome son of her family's rivals"--